2018
DOI: 10.1186/s12885-018-4241-9
|View full text |Cite
|
Sign up to set email alerts
|

Shorter survival in adolescent and young adult patients, compared to adult patients, with stage IV colorectal cancer in Japan

Abstract: BackgroundThe incidence of colorectal cancer in adolescent and young adult patients is increasing. However, survival and clinical features of young patients, especially those with stage IV disease, relative to adult patients remain unclear.MethodsThis retrospective single-institution cohort study was conducted at a tertiary care cancer center. Subjects were 861 consecutive patients who were diagnosed with stage IV colorectal cancer at the age of 15 to 74 years and who were referred to the division of surgery o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 21 publications
(22 reference statements)
0
19
1
Order By: Relevance
“…For example, Quah et al, 24 in a study conducted at the Memorial Sloan Kettering Cancer Center in the United States, found that patients aged 40 years were more likely to have left-sided tumors. Some studies report poor prognosis in young adults diagnosed with CRC attributable to tumor variables such as signet-ring cell or mucinous adenocarcinoma histological type 25 or to poor differentiation. 26 However, no significant difference in these tumor variables was observed between patients with young-onset CRC versus older patients with CRC in our study, in contrast to most published studies.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Quah et al, 24 in a study conducted at the Memorial Sloan Kettering Cancer Center in the United States, found that patients aged 40 years were more likely to have left-sided tumors. Some studies report poor prognosis in young adults diagnosed with CRC attributable to tumor variables such as signet-ring cell or mucinous adenocarcinoma histological type 25 or to poor differentiation. 26 However, no significant difference in these tumor variables was observed between patients with young-onset CRC versus older patients with CRC in our study, in contrast to most published studies.…”
Section: Discussionmentioning
confidence: 99%
“…We systematically retrieved 37 articles describing the prognosis of EO‐CRC compared with older patients (Abdelsattar et al ., ; Blanke et al ., ; Boyce et al ., ; Chandrasinghe et al ., ; Chou et al ., , ; Damodaran and Seshadri, ; Fu et al ., ; Fu et al ., ; Haleshappa et al ., ; Hawk et al ., ; Hubbard et al ., ; Josifovski et al ., ; Khan et al ., ; Kim et al ., ; Kneuertz et al ., ; Kolarich et al ., ; Li et al ., ; Lieu et al ., ; Manjelievskaia et al ., ; McMillan and McArdle, ; Murata et al ., ; O'Connell et al ., ; Orsini et al ., ; Pokharkar et al ., ; Quah et al ., ; Rho et al ., ; Rodriguez et al ., ; Shen et al ., ; Shida et al ., ; Sultan et al ., ; Vatandoust et al ., ; Wang et al ., ,; Yang et al ., ; You et al ., ; Zhao et al ., ). EO‐CRC survival data are conflicting.…”
Section: Methodsmentioning
confidence: 99%
“…EO‐CRC survival data are conflicting. Some studies indicate a poorer prognosis (Bleyer et al ., ; Khan et al ., ; Lieu et al ., ; McMillan and McArdle, ; O'Connell et al ., ; Shida et al ., ; Sultan et al ., ), whereas others support a comparable or even better prognosis in comparison with older patients (Blanke et al ., ; Hubbard et al ., ; Kneuertz et al ., ; Kolarich et al ., ; McMillan and McArdle, ; O'Connell et al ., ; Quah et al ., ; Rodriguez et al ., ; Vatandoust et al ., ; Wang et al ., ; You et al ., ; Table ). From 1973 to 2005, adult CRC survival outcome improved, whereas child and adolescent CRC survival have not (Sultan et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…Estimation of overall survival (OS) and multivariate analysis were performed as described previously [21, 22]. Briefly, OS was defined as the interval between the date of diagnosis of brain metastases and the date of death from all causes or date of last follow-up for survivors.…”
Section: Methodsmentioning
confidence: 99%